2020
DOI: 10.1080/07853890.2020.1799241
|View full text |Cite
|
Sign up to set email alerts
|

Impact of multimorbidity and polypharmacy on the management of patients with atrial fibrillation: insights from the BALKAN-AF survey

Abstract: Objective: We investigated the impact of multimorbidity and polypharmacy on the management of atrial fibrillation (AF) patients in clinical practice and assessed factors associated with polypharmacy and oral anticoagulation (OAC) use in AF patients with multimorbidity and polypharmacy. Methods: A 14-week prospective study of consecutive non-valvular AF patients was performed in seven Balkan countries. Results: Of 2712 consecutive patients, 2263 patients (83.4%) had multimorbidity (AF þ !2 concomitant diseases)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
(43 reference statements)
0
16
0
1
Order By: Relevance
“…While an increased risk of falls is a well-known and frequently inappropriate reason to withhold oral anticoagulation in patients with AF, 21 recent registry data demonstrated that multimorbidity and polypharmacy are also common reasons cited for the non-use of oral anticoagulants (OACs). 22 …”
Section: Frail Patients With Atrial Fibrillationmentioning
confidence: 99%
“…While an increased risk of falls is a well-known and frequently inappropriate reason to withhold oral anticoagulation in patients with AF, 21 recent registry data demonstrated that multimorbidity and polypharmacy are also common reasons cited for the non-use of oral anticoagulants (OACs). 22 …”
Section: Frail Patients With Atrial Fibrillationmentioning
confidence: 99%
“…Multimorbidity was defined as ≥2 comorbidities at admission. These cutoffs were based on a similar prior analysis (7). And based on the number of concomitant medications, polypharmacy in our study was defined as ≥5 medications.…”
Section: Patients Selectionmentioning
confidence: 99%
“…These patients have poor survival and higher stroke and bleeding risks compare with AF patients without multimorbidity (5), which poses a significant burden to patients, families, physicians, and global healthcare systems (3). The number of comorbidities directly related to polypharmacy (concomitant use of ≥ 5 medications) (6), and it reported that polypharmacy prevalence in AF has ranged from 40 to 95% (7). The high prevalence of polypharmacy increases further complexity to the management of AF patients.…”
Section: Introductionmentioning
confidence: 99%
“…При этом в наблюдательных исследованиях показано, что пациенты с ФП и ОКС реже получают соответствующую антитромботическую терапию [28] и чаще подвержены неблагоприятным исходам [29], чем пациенты с ОКС без ФП. В регистре BALKAN-AF, включавшем 2712 больных ФП, показано, что у коморбидных пациентов с ФП антитромботическая терапия была неоптимальной, и 18% коморбидных пациентов не получали антикоагулянты, при этом наличие ИБС и перенесенного ИМ были независимыми предикторами отсутствия назначения ОАК у коморбидных пациентов с впервые выявленной ФП [30].…”
Section: материал и методыunclassified